Sharing health information online in South Korea: motives, topics, and antecedents. (11th October 2017) - Kye, S Y; Shim, M; Kim, Y C; Park, K
Abstract: This study aimed to examine the motives, topics and antecedents for sharing health information online among Korean Internet users. Eight hundred adults completed a web-based survey exploring the motives; topics; physical, cognitive, affective and environmental factors; and experiences relating to sharing health information online. The motives for not sharing information included information absence and inappropriateness. The most preferred topic was disease. Good subjective health was significantly associated with frequent information sharing while individuals with a history of disease involving themselves or family members were more likely to share health information than were those without such a history. Further, a higher level of depressed mood was related to a higher level of sharing. Internet-related self-efficacy and trust in information delivery channels were positively related to sharing. Future research could extend the factors related to information sharing to include the evaluation of shared information.